Mental health disorders and quality of life among Saudi women who have experienced domestic violence - AL-shahrani, Hend Faye; Hammad, Mohammad Ahmed (Frontiers in Public Health, 2025)
ObjectiveThe present cross-sectional study aimed to examine the nature of domestic violence among women in Saudi Arabia, to explore its association with mental health disorders such as depression and anxiety, and to examine its impact on victims’ quality of life.MethodsThis cross-sectional descriptive study was conducted in Riyadh region, Saudi Arabia. Data were collected from 387 women from the Riyadh region who had experienced domestic violence (Mean age = 32.47 years; SD = 4.26 years) using a systematic random sampling method. Quantitative data were gathered using the Domestic Violence Scale, the Depression Scale (CES-D-10; Andresen et al., 1994), the General Anxiety Scale (GAD-7; Spitzer et al., 2006), and the Quality of Life Scale (WHOQOL-BREF; Group, 1998).ResultsThe results revealed that 36.68% of the participants experienced moderate to severe levels of domestic violence. Psychological violence was more common than physical violence, while sexual violence was the least prevalent. Additionally, employed, more educated, and older women tended to experience lower levels of domestic violence as compared to their counterparts. Moreover, women who had experienced domestic violence exhibited higher severity of depression and anxiety symptoms. A linear regression analysis indicated that domestic violence was a powerful predictor of depression, anxiety, and poor quality of life in this sample.ConclusionThese findings highlight the need to further examine the adverse effects of domestic violence on women and their children, and to prioritize mental health and quality of life interventions for such women. The insights gained from this study could also inform the design of programs aimed at preventing domestic violence.